Settlement of Rejection of Land Acquisition Activities According to Fiqh and Indonesian Law - Artiyanto, Artiyanto; Purwandari, Elce; Husni, Husni (Rechtsvinding, 2025)
This research aims to formulate a mechanism for resolving objections from land rights holders to land procurement activities intended for public purposes. Employing a qualitative approach and literature study, this research is guided by Maslahat Theory with a comparative approach. It relies on secondary data, including primary, secondary, and tertiary legal materials. The study reveals that objections to land procurement activities have existed since the early period of Islam, notably during the times of Prophet Muhammad SAW and al-Khulafā' ar-Rāshidun. Fiqh does not provide a standardized mechanism for resolving land rights holders' objections to land procurement, instead leaving resolution to government policy based on the broader benefits of the state and religion, ensuring land rights holders are not oppressed or harmed. Based on resolutions used by early Islamic caliphs, this research identifies three resolution methods: discussion and dialogue, tahkim (arbitration), and court proceedings. Implementing these three methods is entrusted to the government, tailored to local customs (uruf) and the evolving dynamics of land procurement regulations for public purposes. In Indonesia, objections to land procurement activities are comprehensively regulated, notably through Law No. 2 of 2012 on Land Procurement for Development in the Public Interest.